Challenges of Seed Potato (Solanum tuberosum L.) Production and Supply System in Bangladesh - A Review (The Agriculturists, 2016)
Potato (Solanum tuberosum L.) is an important vegetable that plays a vital role in global food and nutritional security and alleviation of poverty, especially in Bangladesh. Although, the soil and climatic conditions of  Bangladesh are favourable for potato cultivation, every year production is hampered due to use of low quality seeds. Seed potato industry is developing in Bangladesh. However, only 5-10% quality seeds are being produced and used by the potato farmers. Quality seeds alone can contribute to increased yield by 15-20%. Both public and private sectors together supply only 5% quality seed potato and the rest 95% is almost of low quality produced by the farmers themselves. In prioritizing different issues of agriculture, challenges of production and supply of quality seed to the farmers should be considered as a top priority issue. For increasing quality seeds, the whole seed system needs to be reviewed. The present work was an attempt to review the seed potato production systems, supply system  and also to identify the possible challenges and policy implications in regards of the problems on seed potato in Bangladesh.The Agriculturists 2015; 13(1) 173-188